1999
DOI: 10.1088/0953-8984/11/39/308
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band structure of magnesium and magnesium oxide: experiment and theory

Abstract: Electron momentum spectroscopy (EMS) has been used to measure the valence band electronic structure of thin magnesium and magnesium oxide films. The band structures have also been calculated within the linear muffin-tin orbital (LMTO) approximation. The free-electron-like parabola characteristic of metallic solids was observed for magnesium with a bandwidth of approximately 6 eV, in agreement with previous measurements. The inclusion of energy broadening due to finite hole-lifetime effects and a Monte Carlo si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
4
19
1
Order By: Relevance
“…Hence there is a shift of about 2 eV in positions of the corresponding p-band peaks. A similar increase of the experimental bandgap was observed in our previous measurements of MgO [31] and BeO [51]. This discrepancy seems to be due to the failure of the LDA approximation to correctly describe electron correlation effects in insulating solids.…”
Section: Valence Bandsupporting
confidence: 85%
See 3 more Smart Citations
“…Hence there is a shift of about 2 eV in positions of the corresponding p-band peaks. A similar increase of the experimental bandgap was observed in our previous measurements of MgO [31] and BeO [51]. This discrepancy seems to be due to the failure of the LDA approximation to correctly describe electron correlation effects in insulating solids.…”
Section: Valence Bandsupporting
confidence: 85%
“…The theory changes from 0.2 to 1.6 over the same momentum range. We observed a similar disagreement in the relative p-to -s-band EMD ratio for MgO [31] and BeO [51,52].…”
Section: P-bandsupporting
confidence: 66%
See 2 more Smart Citations
“…Canney et al studied electronic band structure of thin magnesium and magnesium oxide films, experimentally and theoretically. They showed that the investigated band structures of Mg and MgO have the characteristic of a metallic and ionic solid, respectively [19]. Phuoc et al synthesized Mg/MgO nanocrystallites by laser ablation of magnesium in acetone and isopropanol with a Q-switched Nd-Yag laser operating at 1064 nm and investigated structural properties of the formed Mg/MgO nanostructures [20].…”
Section: Introductionmentioning
confidence: 99%